The Archival Turn in Feminism : Outrage in Order - Eichhorn, Kate, 1971- (Book collections on Project MUSE., 2013)
In the 1990s, a generation of women born during the rise of the second wave feminist movement plotted a revolution. These young activists funneled their outrage and energy into creating music, and zines using salvaged audio equipment and stolen time on copy machines. By 2000, the cultural artifacts of this movement had started to migrate from basements and storage units to community and university archives, establishing new sites of storytelling and political activism. This book chronicles these important cultural artifacts and their collection, cataloging, preservation, and distribution. The author, a cultural studies scholar, examines institutions such as the Sallie Bingham Center for Women's History and Culture at Duke University, The Riot Grrrl Collection at New York University, and the Barnard Zine Library. She also profiles the archivists who have assembled these significant feminist collections.--publisher's website.